Neural text generation in regulatory medical writing - Meyer, Claudia; Adkins, Daniel; Pal, Koyena; Galici, Ruggero; Garcia-Agundez, Augusto; Eickhoff , Carsten (Frontiers in Pharmacology, 2023)
Background. A steep increase in new drug applications has also increased the overhead of writing technical documents such as medication guides. However, natural language processing can contribute to reducing this overhead. Objective. To generate medication guides from texts that relate to prescription drug labeling information. Materials and Methods. We collected official drug label information from the DailyMed website. We focused on those drug labels containing medication guide sections to train and test our model. To construct our training dataset, we aligned “source” text from the document with similar “target” text from the medication guide using three families of alignment techniques: global, manual, and heuristic alignment. The resulting source-target pairs were provided as input to a Pointer Generator Network, an abstractive text summarization model. Results. Global alignment produced the lowest ROUGE scores and relatively poor qualitative results, as running the model frequently resulted in mode collapse. Manual alignment also resulted in mode collapse, albeit higher ROUGE scores than global alignment. Within the family of heuristic alignment approaches, we compared different methods and found BM25-based alignments to produce significantly better summaries (at least 6.8 ROUGE points above the other techniques). This alignment surpassed both the global and manual alignments in terms of ROUGE and qualitative scoring. Conclusion. The results of this study indicate that a heuristic approach to generating inputs for an abstractive summarization model increased ROUGE scores, compared to a global or manual approach when automatically generating biomedical text. Such methods hold the potential to significantly reduce the manual labor burden in medical writing and related disciplines.